(3MGTjI Ydi TQM TjN GdESdGe dEjSGZhLjs - (3GdOdLj, eMeO Hf EHQGgjes ((3YHO GdbGOQ Hf GdNWjHs)
(3ChdgG (B:s
(3HYO GdHSedI ; MeOG def fWbJ GdehLhOGJ hHYO ajbhd eMeO Hf EHQGgje GdOdLj gPG JYdjb Ydi TQM TjN GdESdGe deJf EjSGZhLjs
(3BNQgG (B:s
(3HGdfSHI gh GdHQgGf abW dGfg jajO Gdjbjf HdG QjH HNdGa GdBNQjf hCeG GdGSJbQGQ hGdJeKjd ageG edMbGf HGdbjGS aj GdMce hGdJChjds
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eMeO CHh GdNjQ aJM Gddg eY NJe (B: 1274 (3g`s
Keywords: (3GdadSaI hGdefWbs